Comparison between effect of desflurane/remifentanil and propofol/remifentanil anesthesia on somatosensory evoked potential monitoring during scoliosis surgery—A randomized controlled trial - Hasan, Mohd Shahnaz; Tan, Jin Keat; Chan, Chris Yin Wei; Kwan, Mun Keong; Karim, Fathil Syafiq Abdul; Goh, Khean Jin (SAGE Publications (UK and US), 2018)
Background: Drugs used in anesthesia can affect somatosensory evoked potential (SSEP) monitoring, which is used routinely for intraoperative monitoring of spinal cord integrity during spinal surgery. Objective: The objective of this study was to determine whether combined total intravenous anesthesia (TIVA) technique with propofol/remifentanil is associated with less SSEP suppression when compared to combined volatile agent desflurane/remifentanil anesthesia during corrective scoliosis surgery at a comparable depth of anesthesia. Design: It is a randomized controlled trial. Setting: The study was conducted at the Single tertiary University Hospital during October 2014 to June 2015. Patients: Patients who required SSEP and had no neurological deficits, and were of American Society of Anesthesiologist I and II physical status, were included. Patients who had sensory or motor deficits preoperatively and significant cardiovascular and respiratory disease were excluded. A total of 72 patients were screened, and 67 patients were randomized and allocated to two groups: 34 in desflurane/remifentanil group and 33 in TIVA group. Four patients from desflurane/remifentanil group and three from TIVA group were withdrawn due to decrease in SSEP amplitude to <0.3 µV after induction of anesthesia. Thirty patients from each group were analyzed. Interventions: Sixty-seven patients were randomized to receive TIVA or desflurane/remifentanil anesthesia. Main outcome measures: The measurements taken were the amplitude and latency of SSEP monitoring at five different time points during surgery: before and after the induction of anesthesia, at skin incision, at pedicle screw insertion, and at rod insertion. Results: Both anesthesia techniques, TIVA and desflurane/remifentanil, resulted in decreased amplitude and increased latencies of both cervical and cortical peaks. The desflurane/remifentanil group had a significantly greater reduction in the amplitude (p = 0.004) and an increase in latency (p = 0.002) of P40 compared with the TIVA group. However, there were no differences in both amplitude (p = 0.214) and latency (p = 0.16) in cervical SSEP between the two groups. Conclusions: Compared with TIVA technique, desflurane/remifentanil anesthesia caused more suppression in cortical SSEP, but not in cervical SSEP, at a comparable depth of anesthesia.